Analysis of Different Production Systems in Laying Hen Enterprises with Analytic Hierarchy Process in Turkey - Tuncel, S.; Sipahi, C.; Akcay, A.; Altin, O.; Sariozkan, S.; Gokdai, A.; Arikan, M. S. (Facta-Fundacio Arnco Ciencia Tecnologia Avicolas, 2021)
The present study aimed to evaluated the enterprises engaged in conventional cage, enriched cage, free-range and organic egg production in Turkey in terms of four different criteria (profit, investment cost, animal welfare/health and sales/marketing) using the Analytical Hierarchy Process (AHP). For this purpose, the questionnaires through face-to-face interviews were conducted with a total of 64 producers who had been determined by random sampling method from 5 different regions included 17 Provinces between November 2016 and March 2019, and primary data were obtained. As a result, it has been found strategically significant that enterprises, to be engaged at the level of 47.0%, 20.0%, 18.0% and 15.0% in conventional, enriched, free-range and organic cage systems, respectively, in the market in terms of profit, investment cost, animal welfare/health and sales /marketing criteria. In addition, in the enterprises within the scope of the research, the profit, investment cost, sales/marketing and animal welfare/health criteria were determined as the dominant criteria at the level of 53.5%, 22.0%, 13.5% and 11.0% respectively. In conclusion, the conventional cage system is dominant with the rates of 55.0% for profit and 53.0% for investment cost criteria, and both of the conventional and enriched systems in terms of sales/marketing criteria are 38.5% dominant and the organic system in terms of animal welfare/health is 46.0% dominant.
Keywords: Analytical hierarchy process; commercial laying enterprises; egg; organic system; traditional cage system